Problems in Making Power of Attorney Burden Mortgage Rights - Sukarman Sukarman (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
In its development, in terms of making a Deed of Granting Mortgage the debtor cannot attend which is then represented by his representative, the consequence of the debtor's representative is that the Deed of Granting Mortgage Rights must be drawn up with a Power of Attorney to impose Mortgage Rights. This research uses a normative juridical approach, the results of the study state that the factors that influence the emergence of problems in making a power of attorney to impose a mortgage are in the form of laws and regulations, namely in the form of disharmony between Article 38 of the Notary Position Law and Article 96 paragraph (1) of the Head Regulation. National Land Agency Number 8 of 2012, the weakness factor of the Power of Attorney to impose mortgage rights, namely the validity period of the power of attorney to impose mortgage rights and additional costs in making a power of attorney to impose mortgage rights which is also a notary certificate.